1994
DOI: 10.1007/bf01737426
|View full text |Cite
|
Sign up to set email alerts
|

Multiple autoantibody production in a patient with splenic lymphoma

Abstract: We report on a patient with splenic lymphoma of B-cell origin who developed autoimmune hemolytic anemia (AIHA). IgM lambda M-protein, IgM anticardiolipin antibody (ACA), and lupus anticoagulant (LA) were detected in the serum, and direct Coombs' test showed autoantibodies of the IgG1 and IgG2 subclasses on red blood cells (RBC). In in vitro culture, tumor cells isolated from the spleen produced only IgM ACA, which was enhanced by IL-6 but not by IL-4 or IL-5. The levels of ACA and LA decreased after splenectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The expression of a limited repertoire of immunoglobulin VH-and VL-genes by HCV-associated lymphoma B-cells due to viral E2 antigenic stimulation can lead to the development of autoimmunity [150,151]. Moreover, viral antigen can promote production of certain cytokines that are involved in B-cell terminal differentiation via autocrine or paracrine mechanisms e.g., IL-6 can facilitate differentiation of lymphoma cells into antibody-producing cells and, thereby, autoimmunity [152,153].…”
Section: Autoimmunity and Non-hodgkin Lymphomamentioning
confidence: 99%
“…The expression of a limited repertoire of immunoglobulin VH-and VL-genes by HCV-associated lymphoma B-cells due to viral E2 antigenic stimulation can lead to the development of autoimmunity [150,151]. Moreover, viral antigen can promote production of certain cytokines that are involved in B-cell terminal differentiation via autocrine or paracrine mechanisms e.g., IL-6 can facilitate differentiation of lymphoma cells into antibody-producing cells and, thereby, autoimmunity [152,153].…”
Section: Autoimmunity and Non-hodgkin Lymphomamentioning
confidence: 99%
“…The presence of aCL antibodies has been described in patients with NHL [19][20][21][22]. aCL antibodies are related to NHL, this is supported by the theory indicated that aCL antibodies are produced by the lymphoma cells [23].…”
Section: Introductionmentioning
confidence: 77%
“…aCL antibodies are related to NHL, this is supported by the theory indicated that aCL antibodies are produced by the lymphoma cells [23]. An approximately 30% prevalence of anticardiolipin antibodies in patients suffering from non-Hodgkin's lymphomas has been reported [24].…”
Section: Introductionmentioning
confidence: 82%
“…In the last years a higher prevalence of aPL antibodies was observed in patients with solid tumours compared to controls (Zuckerman et al, 1995) and in patients with haematological malignancies (Pusterla et al, 2004). The reasons of this increased antibody production are only partially clarified: their production may be induced by particular immunotherapy of cancer such as interferon (Becker et al, 1994) or started by immune system response to new tumour antigens (Sawamura et al, 1994). In particular it is possible that autoantibodies to malignant cells arise secondary to changes in the cell membrane that induce exposure of certain antigens that are normally facing the intracellular compartment (Reinstein & Shoenfeld, 2007), then activating pathogenetic autoreactive human T cells (Yamaguchi et al, 2007).…”
Section: Antiphospholipid Antibodiesmentioning
confidence: 99%